Species composition, richness, and biomass of understory vegetation influence the gall rust disease incidence and severity in Falcataria falcata L. Greuter and R. Rankin plantation - Ramoncito, Nomar A.; Jawani, Rovana M.; Rojo, Mark Jun A.; Tulod, Adrian M. (2025)
Gall rust remains a significant challenge for Falcataria falcata plantations in the Philippines,
significantly impacting tree health and overall plantation productivity. This research aimed to
evaluate several understory vegetation parameters such as species composition, species richness, and biomass to determine how these factors relate to the severity of gall rust disease within a F. falcata stand. The findings indicate that exotic species, while prevalent, did not uniformly dominate across all vegetation classes. Imperata cylindrica and Saccharum spontaneum emerged as the two most dominant species. In contrast, medium and high vegetation layers exhibited a mix of both native and exotic species. Among these, Piper aduncum and Melastoma malabathricum attained high importance value index (IVI) scores. Further analysis revealed a strong correlation between gall rust severity and understory biomass and species richness. Specifically, medium and high vegetation layers – which had greater biomass and more diverse species assemblages – experienced notably higher levels of gall rust infection. The most severe disease symptoms were observed within biomass densities ranging from 2–4 kg/m². These results underscore the crucial need to manage understory vegetation composition, particularly by balancing the proportion of exotic and native species, to mitigate gall rust outbreaks. By carefully regulating biomass density and levels of species richness, plantation managers could enhance F. falcata stand health and reduce the risks associated with this destructive fungal disease.
Keywords: Biomass; Vegetation & climate